Positive Correlation Between LTA Expression and Overall Immune Activity Suggests an Increased Probability of Survival in Uterine Corpus Endometrial Carcinoma - Shi, Mingjie; Luo, Fei; Shao, Taotao; Zhang, Hengli; Yang, Taili; Wei, Yue; Chen, Riling; Guo, Runmin (Frontiers in Cell and Developmental Biology, 2022)
Mounting evidence indicates that immune status plays a crucial role in tumor progress and metastasis, while there are no effective and easily assayed biomarkers to reflect it in uterine corpus endometrial carcinoma (UCEC) patients. Here, we attempted to identify the potential biomarkers that were differentially expressed between normal- and tumor tissues and involved in prognosis, immune microenvironment of UCEC patients. RNA-seq data with relevant clinical information were obtained from the cancer genome atlas (TCGA). ssGSEA algorithm was applied to calculate the enrichment scores of every tumor infiltration lymphocyte (TIL) set in each sample, and patients were then divided into three clusters using multiple R packages. Cox analysis, ESTIMATE and CIBERSORT and were utilized to determine the differentially expressed immune-related genes (DEIG) with overall survival, and to explore their roles in prognosis, immune microenvironment and immunotherapeutic response. The TIMER and TISIDB databases were utilized to predict the effectiveness of immunotherapy in UCEC patients. LTA was finally identified to be significantly upregulated in tumor tissues and closely associated with prognosis and immunological status, which was then verified in GSE17025. In multivariate analysis, the hazard ratio of LTA was 0.42 with 95% CI (0.22–0.80) (P = 0.008). Patients with high LTA expression had better survival and apparently immune-activated phenotypes, such as more tumor mutation burden (TMB), stronger immune cell infiltrations, higher expression of immunosuppressive points and higher immunophenoscore, meaning who had an immunotherapeutic advantage than those with low LTA expression. TIMER and TISIDB indicated LTA was highly expressed in UCEC, and its expression was negatively correlated with stages and positively related to prognosis, respectively. Additionally, we found LTA ectopic expression weakened the proliferation ability of RL95-2 cells. All these findings indicated LTA could as a novel and easily assayed biomarker to predict immunological status and clinical outcomes and even as an antioncogene to explore in-depth in UCEC.